Customer acquisition and retention spending: An analytical model and empirical investigation in wireless telecommunications markets - MIN, Sungwook (Institutional Knowledge at Singapore Management University, 2016)
Strategic resource allocation in growth markets is always a challenging task. This is especially true when it comes to determining the level of investments and expenditures for customer acquisition and retention in competitive and dynamic market environments. This study develops an analytical model to examine firms' investments in customer acquisition and retention for a new service; it develops hypotheses drawing on analytical findings and tests them with firm-level operating data of wireless telecommunications markets from 41 countries during 1999-2007. The empirical investigation shows that a firm's acquisition cost per customer is more sensitive to market position and competition than retention cost per customer. Furthermore, whereas firms leading in market share, on average, do not have a cost advantage over other firms in retaining customers, they have a substantial cost advantage in acquiring customers, and this advantage tends to increase with market penetration. The study results provide guidelines for firms' strategic resource allocation for customer acquisition and retention in competitive service markets.